Stability of FeVO4-II under Pressure: A First-Principles Study - Pricila Betbirai Romero-Vázquez; Sinhué López-Moreno; Daniel Errandonea (Crystals, 2022)
In this work, we report first-principles calculations to study FeVO<semantics>4</semantics> in the CrVO<semantics>4</semantics>-type (phase II) structure under pressure. Total-energy calculations were performed in order to analyze the structural parameters, the electronic, elastic, mechanical, and vibrational properties of FeVO<semantics>4</semantics>-II up to 9.6 GPa for the first time. We found a good agreement in the structural parameters with the experimental results available in the literature. The electronic structure analysis was complemented with results obtained from the Laplacian of the charge density at the bond critical points within the Quantum Theory of Atoms in Molecules methodology. Our findings from the elastic, mechanic, and vibrational properties were correlated to determine the elastic and dynamic stability of FeVO<semantics>4</semantics>-II under pressure. Calculations suggest that beyond the maximum pressure covered by our study, this phase could undergo a phase transition to a wolframite-type structure, such as in CrVO<semantics>4</semantics> and InVO<semantics>4</semantics>.